Degradação de biossólido por fungos lignocelulolíticos - Menezes, Fábio Pacheco (2013)
The treatment of wastewater in the Santa Maria city (RS) is the type of extended aeration activated sludge. In this process are generated solid waste (biosolids) requiring final disposal. In the chemical composition of biosolids are found organic compounds derived from cell wall of plants. Among these, stand out the hemicellulose, cellulose and lignin, since the degradation of these fractions is not effective in biological reactors. Few organisms are able to act simultaneously on these three fractions, due to its recalcitrance. However, certain white rot fungi timber assemblies have enzymatic components capable of degrading plant, in particular the lignocellulosic fibers. Therefore, it is assumed that the basidiomycetous fungi that cause white rot can be used to promote biodegradation of extended aeration activated sludge. This study aims to select and evaluate the efficiency of isolates to biodegrade lignocellulolytic activated sludge generated in the Sewage Treatment Station of Santa Maria (RS) aiming to know the degradation rates offered by fungal isolates. The activated sludge was evaluated chemically inorganic fraction to its knowledge of the levels of heavy metals and physicochemical characterization. The lignocellulosic fibers (lignin, hemicellulose and cellulose) were estimated using the method of Von Soest. The basidiomycete fungi were collected in the region of Santa Maria (RS) and isolated in the laboratory to obtain pure cultures. We also evaluated the fungal isolates assigned Cenargem (Brasilia) recognized lignocellulolytic. These organisms were tested for their ability to biodegrade naturally and autoclaved activated sludge by respirometric experiments under different conditions of temperature, humidity and pH. The levels of heavy metals showed that biosolids Station Wastewater Treatment Santa Maria (RS) inset within the limits set by national and international legislation. The physico-chemical parameters were within the expected range for activated sludge with extended aeration. Phosphorus, however, showed high levels due to the use of ferric chloride in the wastewater treatment liquid. Autoclaving of biosolids promoted significant chemical changes in organic and inorganic fractions. The respirometric tests showed different responses to the isolates, the temperature being the most effective environmental factor to increase the rates of biodegradation of activated sludge. The fungal isolates of Schyzophyllum commune and Trametes versicolor showed the highest rates of biodegradation of activated sludge reaching values of 65.71% and 64.74%, respectively. These isolates acted on fractions hemicellulose, cellulose and lignin activated sludge Station Wastewater Treatment Santa Maria (RS) indicating the possibility of using biosolids as degrading.